Inter- and intraspecific patterns in age, morphometrics and mineralization status in the thorny sea pen Pennatula aculeata and the greater sea pen Ptilella grandis - Camille Aubé; Virginie Roy; Piero Calosi (Discover Oceans)
Abstract Sea pens are ecologically important coral species in deep, cold-water ecosystems in the Northwest Atlantic, where they form dense aggregations. Sea pens are threatened by bottom-contact fishing gears and potentially by global change drivers, including ongoing ocean acidification. To better understand their fundamental biology and how these environmental threats may affect sea pens, information on their age structure, growth rates, and level of mineralization is required. We evaluate the age of the sea pens Pennatula aculeata (Danielssen 1860) and Ptilella grandis (Ehrenberg 1834) from two regions of contrasting densities in the Estuary and the Gulf of St. Lawrence. In addition, we characterized relationships between the length, diameter, age, growth rate, and mineralization status of sea pens central stem, known as the rachis. We revealed interspecific differences in age, length, diameter and growth rates, as well as intraspecific (regional) differences in age, length and diameter. On average, the mineral content of longer and older individuals was lower, especially in the upper extremity of the rachis, suggesting a change in mineralization during ontogeny that may have evolved to guarantee greater flexibility of the parts more exposed to currents. There were also interspecific differences in mineralization status, with P. aculeata generally being more highly mineralized.